Resposta :
[tex] > \: resolucao \\ \\ \geqslant \: progressao \: \: geometrica \\ \\ a1 = - 2 \\ q = 2 \\ \\ = = = = = = = = = = = = = = = = = \\ \\ \\ sn = \frac{a1(q {}^{n} - 1)}{q - 1} \\ \\ sn = \frac{ - 2(2 {}^{5} - 1) }{2 - 1} \\ \\ sn = \frac{ - 2(32 - 1)}{1} \\ \\ sn = \frac{ - 2 \times 31}{1} \\ \\ sn = - 62 \\ \\ \\ resposta \: > \: \: letra \: ( \: \: \: b \: \: \: ) \\ \\ \\ \geqslant \leqslant \geqslant \leqslant \geqslant \leqslant \geqslant \leqslant \geqslant [/tex]
![Ver imagem EWERTON197775P7GWLB](https://pt-static.z-dn.net/files/d55/c2b50456a440e5b92401d76060702f97.jpg)